A Literary Review of Garbhashayarbuda in Ayurveda w.s.r. to Uterine Fibroid - Kanwar, Pushp; Dixit, Mahesh; Meena, Narendra Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Uterine fibroids are most common disease of women in reproductive age. Though uterine fibroids are benign in Nature; they reveal a wide range of symptoms like metrorrhagia, dysmenorrhea, menorrhagia, low back pain etc. Morden treatment protocols include hormonal therapy, myomectomy hysterectomy, and uterine artery embolization. Unwillingness for sustained hormone therapy and panic for surgery brings patients towards to Ayurveda. Ayurveda classics mention various pathological conditions that have features similar to fibroids. Ayurveda it is mandatory to know the correlation of uterine fibroids with Garbhashayarbuda. Arbuda is the disease described in Ayurvedic Samhitas and its corresponds to tumours. The treatment is aimed towards reducing the size of fibroids using Ushna, Tikshna, Lekhana Dravyas along with management of symptoms. So this article focuses on potentials of Ayurveda in management of different aspects of uterine fibroid.